Semantic frame as an element of meaning-making - Filateva, Tatyana Vladimirovna (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика, 2023)
Introduction. In the modern socio-cultural space, the concept of the meaning of the text of culture, the process of meaning-making have become relevant among scientists. Previously, these concepts were considered in linguistics, psychology and philosophy, today they have become popular among cultural scientists, and art historians. A theoretical analysis of the concept of “frame” allows us to conclude that a frame is a fragment of a person’s memory, representing knowledge about a particular cultural phenomenon. Consideration of the frame in the structure of meaning-making allowed us to reveal that the frame is a cognitive component of the meaning-forming structure. The semantic frame is associated with the concept of understanding the text of culture, which we designate as an artifact, a semantic model of consciousness. In the presence of semantic experience, it is possible to understand the text of culture. We associate the frame with the practical activity of a person and society, that is, with the meaning given to him in the experience of cultural activity. Conclusion. A semantic frame is an element of meaning-making, since it carries knowledge about a particular cultural phenomenon and allows us to establish the meaning of a given cultural text, its axiological meaning. A frame is a generalized frame of experience, a scheme of practical action in which images are revealed through functions. The truth of the frame is established in practice, since a person is a practical and expedient being.